Professor Pigou's Theory of Unemployment - Harris, S. E. (Quarterly Journal of Economics, 1935)
Introduction, 286. — 1. Elasticity of real demand for labor in a particular occupation, 287. —2. The relation of employment in non-wage-good industries and wage-good industries, 291. — 3. Elasticity of discounting. — The effects on the rate of interest and hence on employment of changes in the wage bill that follow movements in the real rate of wages, 293. — 4. The elasticity of demand for labor over all occupations, 301. — 6. Monetary elasticity of demand for labor, 305. — 6. Factors other than money affecting the level and variations of the real demand for labor, 308. — (a) Variations in demand for durable commodities, 308. — (b) Costs of various methods of state stimulation of emplo3rment, 310. — (c) Employment and the supply of wage-goods, 311. — (d) Special problems relating to the flow of wage-goods, 313. — 7. The difference made by money, 315. — (a) Money and the real demand function for labor, 315. — (b) The removal of some assumptions, 317. — (c) An error in estimating the intervals between receipt and expenditure of income and between expenditure and subsequent reincarnation as new income, 318. — 8. Problems in the causation of unemployment, 319. — Conclusion.